Lighting through educational robotics - Plaza, Pedro; Sancristobal, Elio; Carro, German; Castro, Manuel; Blazquez, Manuel; Garcia-Loro, Felix (2018 XIII Technologies Applied to Electronics Teaching Conference (TAEE), 2018)
Robotics and computational thinking are ideal tools for developing science, technology, engineering and mathematics (STEM) pedagogy. Today, educational robotics tools emerge with the aim of promoting innovation and motivation of students during the learning process. Robots are becoming more common in our daily lives; therefore, it is important to integrate robots into all levels of our society. This demonstrator focuses on driving the same content through three low-cost robotic educational tools. The first is Scratch, where you can schedule interactive stories, games and animations. The second tool is Crumble, an easy-to-use programmable controller. Its programming interface uses a block programming language that facilitates its use. Finally, Arduino is an open source, hardware- and software-based platform that is easy to use and has great potential for developing robotic applications. This demonstrator aims to present the above platforms as educational robotics tools as the first step into the world of robotics. Throughout this demonstrator an introduction to educational robotics is developed.